2011
DOI: 10.1007/s12161-011-9262-9
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Application of a Sample Process Control in Detection of Foodborne Viruses

Abstract: Sample process controls (SPCs) are an essential component of methods to detect viruses in food, as they verify that the sample treatment has operated correctly. Also, the use of an SPC can allow the efficiency of extraction of the target to be estimated for each individual sample analysed. The use of murine norovirus as SPC is here described. Its efficiency of extraction from different food products was 39.47%, 24.79% and 36.29% for strawberry, lettuce and shellfish samples. An incorrectly performed sample tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…Quality control is therefore important in the pre-amplification analytical procedure. The use of a sample process control was reported for assessing the performance of extraction of target viruses from food products like strawberry, lettuce, and shellfish (Diez-Valcarce et al 2011). In this study, we processed food items according to the China Entry-Exit Inspection and Quarantine Industry Standards SNT 2626-2010.…”
Section: Discussionmentioning
confidence: 99%
“…Quality control is therefore important in the pre-amplification analytical procedure. The use of a sample process control was reported for assessing the performance of extraction of target viruses from food products like strawberry, lettuce, and shellfish (Diez-Valcarce et al 2011). In this study, we processed food items according to the China Entry-Exit Inspection and Quarantine Industry Standards SNT 2626-2010.…”
Section: Discussionmentioning
confidence: 99%
“…Upon arrival, untreated wastewater samples were divided into 2 × 40 ml aliquots and stored at −20 °C before use. One aliquot was seeded with a known amount of murine NoV (MNV1), added to the samples as a sample process control (Diez-Valcarce et al 2011; D’Agostino et al 2011), in order to calculate viral recovery efficiency (by quantitative PCR) and check for potential inhibitors (by qualitative PCR). The PCR primers used in the study are shown in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…Nucleic acid extraction and rRT-PCR were performed according to standardized Integrated Monitoring and Control of Foodborne Viruses in European Food Supply Chains protocols. An extraction control virus, murine norovirus (MNoV), was placed in all samples before the lysis step of the extraction (8) to demonstrate the extraction of amplifi able nucleic acid. We performed all rRT-PCRs with an internal amplifi cation control (8).…”
Section: The Studymentioning
confidence: 99%
“…An extraction control virus, murine norovirus (MNoV), was placed in all samples before the lysis step of the extraction (8) to demonstrate the extraction of amplifi able nucleic acid. We performed all rRT-PCRs with an internal amplifi cation control (8).…”
Section: The Studymentioning
confidence: 99%